Plates, laminates and shells : Asymptotic analysis and homogenization - Lewinski, T (Series on Advances in Mathematics for Applied Sciences, 2000)
This book presents a rigorous mathematical treatment of the theory of plates, laminates, and shells using the method of homogenization. It provides a unified framework for analyzing the mechanical behavior of composite and layered structures, bridging the gap between microscopic material properties and macroscopic responses.